(2x-6)/(x)=(x-3)/(3)

Simple and best practice solution for (2x-6)/(x)=(x-3)/(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-6)/(x)=(x-3)/(3) equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

(2*x-6)/x = (x-3)/3 // - (x-3)/3

(2*x-6)/x-((x-3)/3) = 0

(2*x-6)/x+(-1*(x-3))/3 = 0

(3*(2*x-6))/(3*x)+(-1*x*(x-3))/(3*x) = 0

3*(2*x-6)-1*x*(x-3) = 0

9*x-x^2-18 = 0

9*x-x^2-18 = 0

9*x-x^2-18 = 0

DELTA = 9^2-(-18*(-1)*4)

DELTA = 9

DELTA > 0

x = (9^(1/2)-9)/(-1*2) or x = (-9^(1/2)-9)/(-1*2)

x = 3 or x = 6

(x-3)*(x-6) = 0

((x-3)*(x-6))/(3*x) = 0

((x-3)*(x-6))/(3*x) = 0 // * 3*x

(x-3)*(x-6) = 0

( x-3 )

x-3 = 0 // + 3

x = 3

( x-6 )

x-6 = 0 // + 6

x = 6

x in { 3, 6 }

See similar equations:

| (7/2t)-2=(-4)-(7t) | | 8x+5y=186 | | 5x+18x+9=0 | | 4x-2z=44 | | 14+5=5x-6(-3x+15)+5 | | 4-y+x=0 | | 14+5=5x+-6(-3x+15)+5 | | 22-(x+9)=8x-5 | | 9=ab | | 19=5x-6(-3x+15)+5 | | (7x-2)(x-1)=0 | | x-3/5=1/x | | x^2-4x+4=x | | 4r+5=13 | | H=-3x^2+12x | | 1/2(0-8) | | 6-2x=6x-10x+1 | | 25/7-4 | | 4(a-1)-3(2-a)=2 | | 25/7-54 | | 2x+4(9+3x)=66 | | 6y-2=3x+10 | | 3g+6=24 | | y-16-3-y=0 | | -4x(-1)+2y=-30 | | 5x-55=-130 | | y+3z=6 | | 4x(-1)+8y=20 | | 9-n=-5n+7n | | -99+7y=-4y | | 2b+4=2b+7 | | (5)secx+7=0 |

Equations solver categories